TINGKAT KONTAMINASI MIKROBA PADA BEBERAPA UNIT PENGOLAHAN IKAN ASAP PINEKUHE DI KABUPATEN SANGIHE - Ely John Karimela; Jeffri A Mandeno (Fakultas Perikanan dan Ilmu Kelautan, 2019)
One of the products processed by smoked fisheries owned by fishermen regency of Sangihe Island is Pinekuhe. This research aims to determine the level of microbial contamination in the smoked fish Pinekuhe processed fishermen regency of Sangihe Islands. Sampling was taken randomly in some of the fish processing units of Pinekuhe smoke. Observation of the deterioration of the quality of fish products Pinekuhe, observed through the test of Total Plate Count (TPC), total mould, and total of Staphylococcus sp. The results showed that the TPC value of all processors meets SNI standards. TPC value of A, B, C, and D processors, respectively, 1,3 x 104 CFU/G, 2,6 x 104 CFU/G, 6,9 x 104, and 1,2 x 104 CFU/g. The total observation of Staphylococcus sp. on processor A and processor B generates a value of 0, while processor C has a total value of 1.1 x 102 TVC/G and processor D has a total value of Staphylococcus sp. 1,2 x 102 TVC/g. The total number of bacteria, the total amount of mould, and the total number of Staphylococcus sp. Still qualify SNI, except Staphylococcus sp. on processor C and processor D exceeds the amount required by the Indonesian National Standard on the limits of contamination microbes in smoked fish.